Peran Nasionalisme dalam Kemandirian Bangsa dan Kemandirian Industri Pertahanan - Moh. Fakhruddin Farhan (Prodi PPkn Universitas Slamet Riyadi, 2022)
Nationalism is a form of ideology that places the highest love, loyalty, and commitment on the nation-state. The concept of nationalism leads to the desire to live together as a nation that has goals and aspirations to be achieved together. Nationalist understanding and behavior must be based on the awareness of being part of a nation and oriented toward achieving common national goals. In the context of practicing nationalism and supporting national defense, the defense industry is a vital strategic industry to pay attention to. The defense industry is engaged in the area of ​​national defense-supporting products. With the arrival of the 4.0 industrial revolution era, the defense industry cannot remain silent and requires adaptation in its application both in the production of defense products and in their use to support national defense. Nationalism is the basis for the development of national independence as the main capital for realizing the ideals of independence, namely becoming an independent, sovereign, and prosperous nation. For this reason, the independence of the defense industry is an implementation of nationalism and part of the national defense strategy in dealing with state threats that are always developing in tandem with technological developments. The independence of the defense industry must be implemented and fully supported by the government and related parties so that it can play a role in realizing the aspirations of the nation and fostering a spirit of nationalism for the Indonesian people.